Pengaruh Kepemimpinan Manajerial, Kepemilikan Institusional, Dan Return On Asset Terhadap Nilai Perusahaan (Studi pada Perusahaan Makanan & Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 ) - Nurmala Yunita; Muhammad Agus Salim; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to analyze the effect of managerial ownership, institutional ownership, and return on asset on the value of the company in food & beverage companies listed on the IDX in 2017 to 2019 using a quantitative approach method.. The population used is food & beverage sector companies listed on the Indonesia Stock Exchange for the period 2017 to 2019 totaling 20 companies. While the sample used in this study used purposive sampling so that based on predetermined criteria, 10 companies were selected as research samples. The analysis used is multiple linear regression. Through this study it can be concluded that managerial ownership ,institutional ownership and return on asset have a significant effect on the value of the company..Keywords: Managerial Ownership, Institutional Ownership, Return On Asset, and the value of the Company